2018
DOI: 10.1155/2018/5041724
|View full text |Cite
|
Sign up to set email alerts
|

Fever of Unknown Origin as a Sole Presentation of Subacute Thyroiditis in an Elderly Patient: A Case Report with Literature Review

Abstract: An 80-year-old Caucasian male presented with fever of 3-week duration. Outpatient workup for infectious etiologies was negative and due to persistent fever, he was hospitalized for further evaluation of fever of unknown origin (FUO). Physical examination and laboratory studies remained unremarkable; however a follow-up CT scan of chest, abdomen, and pelvis with contrast done to rule out malignancy as an underlying cause of FUO revealed heterogeneous thyroid gland with surrounding hazy changes suggestive of thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 23 publications
1
26
0
2
Order By: Relevance
“…Most patients with SAT have negative antithyroglobulin antibodies and antithyroid peroxidase antibodies as opposed to painless thyroiditis in which 50% of patients have positive antibodies (3,11). Both antibodies were negative in our case, making silent thyroiditis less likely.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Most patients with SAT have negative antithyroglobulin antibodies and antithyroid peroxidase antibodies as opposed to painless thyroiditis in which 50% of patients have positive antibodies (3,11). Both antibodies were negative in our case, making silent thyroiditis less likely.…”
Section: Discussionmentioning
confidence: 53%
“…thyroid storm, adrenal crisis, and pheochromocytoma). However, FUO as the sole presenting feature is very rare with only a few reported cases in the literature ( 1 , 3 ). The endocrine disorder most likely to present as an FUO is subacute thyroiditis (SAT); however, telltale findings in these reported cases often point to this disorder ( 4 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, one study showed superiority of steroid use in SAT in patients who fail to achieve clinical remission with NSAIDs 22 . Long term follow-up of patients presenting with SAT is needed to assess for development of permanent hypothyroidism which may occur post transient thyrotoxicosis in around 25 percent of patients requiring treatment with levothyroxine 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The patient’s daughter was very involved in the care. At the first telemedicine session, I discussed that fever can be the main or even the only symptom of subacute thyroiditis but occult infections have to be further ruled out before corticosteroid treatment is initiated ( 3 ). As he did not respond to ibuprofen and propranolol and I could not do a physical examination, I ordered a fluorodeoxyglucose positron emission tomography (FDG PET) and thyroid ultrasound, otherwise not required for subacute thyroiditis diagnosis and management, which were done on the next day.…”
mentioning
confidence: 99%